Analysis Of Influence Of Capital Structure On Corporate Value In PT Astra International Tbk - Wiwin Suryani; Puji Muniarty (Tirtayasa Ekonomika, 2020)
This study aims to determine whether there is an influence of capital structure on company value at PT Astra Internasional Tbk. The population used in this research is the balance sheet financial report data for 10 years from 2009 to 2018. The sample used was 7 years, from 2012 to 2018. The sampling technique used was purposive sampling method. The data analysis technique used is simple linear regression analysis, simple correlation, coefficient of determination, and t-test. The results of the study note that there is no significant and insignificant effect between capital structure on firm value. The results showed that there was no significant and insignificant effect between capital structure and firm value.